Analysis Of The Relationship Of Covid-19 Symptoms Which Receive Favipiravir And Length Of Treatment In The Inpatition Of Dr. Iskak Tulungagung - Aghnia Fuadatul Inayah; Ghassani Shabrina Putri; Amaliyah Dina Anggraeni (Eduvest - Journal of Universal Studies, 2024)
Coronavirus disease 2019 or commonly called COVID-19 is an infectious disease caused by SARS-CoV-2. Favipiravir is a broad-spectrum antiviral drug so it has potential antiviral action against SARS-CoV-2 which is an RNA virus. This research aims to find out the relationship between Covid-19 symptoms when receiving favipiravir and the length of treatment of patients hospitalized at RSUD Dr. Iskak Tulungagung. Observational research with descriptive retrospective methods in COVID-19 patients' moderate symptoms with Favipiravir therapy at RSUD dr. Iskak Tungagung period July - September 2021. Data collection using the calculation of the Slovin formula to determine the number of patient samples. Analysis analysis using SPSS by carrying out the Chi-square test. The results of the study were obtained from 146 patients, the pattern of using Favipiravir was given at a dose (2x1600mg) on the first day followed by (2x600mg) on the second day and so on with the most giving range of 1-7 days .